ENTREPERNERSHIP OF SCRAP DEALERS AND ROLE OF RAG PICKERS A CASE STUDY IN PUDUCHERRY (International Journal of Food and Nutritional Sciences, 2022)
The expansion of urban centers is being rapidly increasing, owing to huge population growth andmigration toward urban centers, resulting in a lack of basic infrastructural facilities such as watersupply, sanitation and sewerage, solid waste management and so on. The scrap dealers and ragpickers plays a vital role in the solid waste management practice. The rag pickers actually goingthrough the dustbins and collecting rags, selling to the scrap dealers and earning the minimumwage sustain their daily needs converting wealth from waste, the scrap dealers were having theirown shops and linkage with the recycling process. This two category of stakeholder’s arestrengthening this recycling process. The scrap dealers were collecting waste from thehouseholds and also collecting from the rag pickers, the scrap dealers are selling the bulk ofwaste scrap’s to the agent of recycling industry and earning income. But the scrap dealersprovide lesser wage to the rag pickers. This paper seek to address the entrepreneurial skill ofscrap dealers and their working modality and profit from waste in Puducherry urban centers wasdiscussed in this paper